Assessment of course-based undergraduate research experiences: a meeting report - Auchincloss, Lisa Corwin; Laursen, Sandra L; Branchaw, Janet L; Eagan, Kevin; Graham, Mark; Hanauer, David I; Lawrie, Gwendolyn; McLinn, Colleen M; Pelaez, Nancy; Rowland, Susan; Towns, Marcy; Trautmann, Nancy M; et al. (CBE life sciences education, 2014)
The Course-Based Undergraduate Research Experiences Network (CUREnet) was initiated in 2012 with funding from the National Science Foundation program for Research Coordination Networks in Undergraduate Biology Education. CUREnet aims to address topics, problems, and opportunities inherent to integrating research experiences into undergraduate courses. During CUREnet meetings and discussions, it became apparent that there is need for a clear definition of what constitutes a CURE and systematic exploration of what makes CUREs meaningful in terms of student learning. Thus, we assembled a small working group of people with expertise in CURE instruction and assessment to: 1) draft an operational definition of a CURE, with the aim of defining what makes a laboratory course or project a "research experience"; 2) summarize research on CUREs, as well as findings from studies of undergraduate research internships that would be useful for thinking about how students are influenced by participating in CUREs; and 3) identify areas of greatest need with respect to CURE assessment, and directions for future research on and evaluation of CUREs. This report summarizes the outcomes and recommendations of this meeting.